A Manhattan information needs snapshot - McNamara, Nicholas (Kansas State University, 2023)
The author conducted the following information ecosystem snapshot in the City of Manhattan, Kansas over a nearly 14-month period starting in Spring 2021 and concluding in Summer 2022. The aim was to get a preliminary understanding of how well local news and information meets residents of African, Asian and Hispanic/Latin descent where they are; find out how well our community participants believed local storytellers and information sources served their interests; whether they believed their communities were understood and reflected in the stories and images of Manhattan as presented by local communicators; and in what ways they believed local news and information flows could be improved in order to better serve Manhattan in its entirety. This qualitative, exploratory study is informed by an understanding of storytelling as central to health and thriving communities. Community stories help people cultivate identity and a sense of place or community (Anderson, 1991), with access to information and networks of discourse serving to empower individuals and communities to take collective action in their own interest as well as uplift one another in times of need. The study employs Communication Infrastructure Theory as its guiding lens (Ball-Rokeach, Kim & Matei, 2001), positing that communities are built around systems of communication that are made up of varying levels of storytelling networks within a unique local infrastructure that directly impacts access to and interplay between networks. This interplays well with the Listening Post Collective’s concept of an information ecosystem, and the study further made use of the LPC Playbook of strategies (Listening Post Collective) for community assessment to help inform its methods of engagement and outreach for this snapshot report. While Manhattan has fared better than many communities in the nation, with more than a fourth of U.S. newspapers going defunct since 2005 (Abernathy et al., 2022), findings from the 2020 Riley County Community Needs Assessment (Gregory et al., 2020) indicating a need for better access to community information and news as well as changing racial and ethnic demographics over the last 10 years locally (U.S. Census Bureau, 2021a) warrants inquiry into how well Manhattan’s storytellers are prepared to serve its proportionally increasing historical minority populations. To begin to get an answer to that question, the study sought a purposive sample of residents of African, Asian, and Hispanic/Latin descent to share their perspective on how well they’ve done thus far. The author spoke with 9 participants through 8 separate interviews – each coming from different backgrounds, working, or leading in different fields, and representing different segments of their respective communities. Participant responses were then analyzed for emergent themes in addition to recommendations for improvement. Some highlights: Residents of African, Asian, and Hispanic/Latin descent face barriers in Manhattan’s storytelling networks. Conversations raised a trio of different barrier subthemes. Participants of Chinese and Hispanic/Latin descent noted that there can be varied access to translated information among local government and community service organizations in Manhattan, effectively closing a door to those residents who only speak languages other than English or speak those languages far better than they do English. Social or interpersonal division was also noted across demographic groups. African American as well as Hispanic/Latin participants told the author about a lack of connective tissue in their communities outside of Kansas State University. Regional and class differences also proved potential sources of interpersonal conflict, which a participant of Chinese descent says impacted her engagement and information sharing in local storytelling networks. Reputation matters. The stories told by local journalistic organizations as well as the accuracy of those stories are remembered by people in the community. When an error is made, it can be hard to move past. Additionally, local media at times has cultivated a reputation for sensation and a focus on issues and voices that often does not include Manhattan’s historical minority communities. Low investment and a lack of understanding is how participants described Manhattan storytellers’ performance in communicating with the city’s minority populaces. Lack of coverage as well as episodic, parachute or shallow reporting was how local news was described to the author across demographics. The same was said for government and community organization outreach, which to varying degrees were described as missing the mark.
Keywords: Media; Journalism; Manhattan; Kansas; BIPOC; Minorities